2004
DOI: 10.1039/b406875k
|View full text |Cite
|
Sign up to set email alerts
|

Chiral ligand exchange capillary electrophoresis using borate anion as a central ion

Abstract: Native DL-pantothenic acid, having a 1,3-diol structure, was chirally resolved by ligand exchange capillary electrophoresis using (S)-3-amino-1,2-propanediol as a chiral selector and the borate anion as a central ion. The optimum conditions for both high resolution and short migration time of DL-pantothenic acid were found to be 200 mM (S)-3-amino-1,2-propanediol and 200 mM borate buffer (pH 9.2) containing 15% methanol with an applied voltage of +25 kV at 20 degrees C, using direct detection at 200 nm. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
(44 reference statements)
0
27
0
Order By: Relevance
“…A comprehensive overview of the selectands involved and the selectors used is given by Schmid et al [77] and Davankov [78]. Recently, Kodama et al [79] have described chiral ligand exchange CE using borate anion as a central ion.…”
Section: Ligand-exchange Cementioning
confidence: 98%
“…A comprehensive overview of the selectands involved and the selectors used is given by Schmid et al [77] and Davankov [78]. Recently, Kodama et al [79] have described chiral ligand exchange CE using borate anion as a central ion.…”
Section: Ligand-exchange Cementioning
confidence: 98%
“…Figure 2 shows the 13 C NMR spectra of D-PTA and the D-PTA-borate-SAP ternary system. We adjusted pH of the solutions to 9.2 consistent with the CE experiments (vide supra) [18] by addition of aqueous NaOH, where carboxyl and amino groups in D-PTA and SAP are considered car- boxylate and ammonium groups, respectively (Fig. 1).…”
Section: Ce Apparatusmentioning
confidence: 98%
“…In the previous work, we introduced borate anion as the central ion of the chiral selector [18]. By using a 1,2-diol, (S)-3-amino-1,2-propanediol (SAP) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations with chiral ligand exchange CE have been described in recent reviews [3][4][5][6]. In these CE studies, copper(II) complexes with amino acids or their derivatives have been widely used as chiral selectors for the enantioseparation of amino acids, their derivatives and a-hydroxy acids, where the ternary copper(II) complexes are formed by the ligand-exchange reaction of the chiral selector with the racemic analyte [7,8].Recently, we found that some diols can be enantioseparated by ligand-exchange CE with borate anion as a central ion of the chiral selector [9,10] with the knowledge that 1,2-and 1,3-diols form considerably stable borate ester complexes in a moderately alkaline aqueous solution [11][12][13][14], where free borate ion, monocyclic and dicyclic (spirocyclic) complexes coexist in the solution [15,16]. By using a 1,2-diol, (S)-3-amino-1,2-propanediol (SAP), DL-pantothenic acid, which has a 1,3-diol structure, was successfully resolved by ligand-exchange CE [9] and the enantioseparation mechanism was also investigated [17].…”
mentioning
confidence: 99%
“…By using a 1,2-diol, (S)-3-amino-1,2-propanediol (SAP), DL-pantothenic acid, which has a 1,3-diol structure, was successfully resolved by ligand-exchange CE [9] and the enantioseparation mechanism was also investigated [17]. Furthermore, neutral 1,2-diol compounds (1-phenyl-1,2-ethanediol, 3-phenoxy-1,2-propanediol and 3-benzyloxy-1,2-propanediol) were enantioseparated by ligand-exchange MEKC using (1S,2S,3R,5S)-pinanediol as a chiral selector ligand [10].…”
mentioning
confidence: 99%